Clustered Cobalt Nanodots Initiate Ferroptosis by Upregulating Heme Oxygenase 1 for Radiotherapy Sensitization. Issue 10 (10th January 2023) - Zhao, Jianqi; Chen, Yin; Xiong, Tainong; Han, Songling; Li, Chenwenya; He, Yingjuan; He, Yongwu; Zhao, Gaomei; Wang, Tao; Wang, Liting; Cheng, Tianmin; Wang, Cheng; et al.
Abstract: High cobalt (Co) levels in tumors are associated with good clinical prognosis. An anticancer regimen that increases intratumoral Co through targeted nanomaterial delivery is proposed in this study. Bovine serum albumin and cobalt dichloride are applied to prepare cobaltous oxide nanodots using a facile biomineralization strategy. After iRGD peptide conjugation, the nanodots are loaded into dendritic mesoporous silica nanoparticles, generating a biocompatible product iCoDMSN. This nanocomposite accumulates in tumors after intravenous injection by deep tissue penetration and can be used for photoacoustic imaging. Proteomics research and molecular biology experiments reveal that iCoDMSN is a potent ferroptosis inducer in cancer cells. Mechanistically, iCoDMSNs upregulate heme oxygenase 1 (HMOX1), which increases transferrin receptors and reduces solute carrier family 40 member 1 (SLC40A1), resulting in Fe 2+ accumulation and ferroptosis initiation. Furthermore, upregulated nuclear factor erythroid 2‐related factor 2 (NRF2), arising from the reduction in Kelch‐like ECH‐associated protein 1 (KEAP1) expression, is responsible for HMOX1 enhancement after iCoDMSN treatment. Owing to intensified ferroptosis, iCoDMSN acts as an efficient radiotherapy enhancer to eliminate cancer cells in vitro and in vivo. This study demonstrates a versatile Co‐based nanomaterial that primes ferroptosis by expanding the labile iron pool in cancer cells, providing a promising tumor radiotherapy sensitizer. Abstract : Dendritic mesoporous silica nanoparticles carrying iRGD peptide‐conjugated CoO@BSA nanodots constitute a tumor‐penetrating nanomaterial iCoDMSN. By decreasing KEAP1 expression and upregulating NRF2 and HMOX1, iCoDMSN expands the labile iron pool in cancer cells and initiates ferroptosis, whereby the nanomaterial sensitizes cancer cells to ionized radiation and eliminates the tumors combined with radiotherapy.